Appearing-disappearing-reappearing Rathke's cleft cyst: An extraordinary finding and review of the literature - Madison Budinich; Jaspreet Johal; Rod J. Oskouian; Krishnamoorthy Thamburaj; R. Shane Tubbs; Elias Rizk (Elsevier, 2016)
Rathke's pouch cysts are uncommonly found on imaging and are usually incidental in nature. Herein, we report a most unusual case of Rathke's pouch cyst verified to have resolved and then 20 years later, to have returned. The germane literature regarding such a phenomenon is reviewed. We believe this to be the first report of a patient with an appearing, disappearing, and reappearing Rathke's cleft cyst. Keywords: Sella turcica, Pituitary gland, Skull base, Anomaly, Imaging